DEVELOPMENT OF LKPD MATERIAL ON BASIC SERVICE TECHNIQUES IN VOLLEYBALL IN GRADE VIII OF NAPALLICIN STATE MIDDLE SCHOOL - Yohana Oktapia; Muhammad Suhdy (CV Grasta Glory, 2026)
This study aims to develop a Student Worksheet (LKPD) on the basic service technique in volleyball for eighth-grade students at SMP Negeri Napallicin using the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. This research is a type of Research and Development (R&D). The validity results showed that the LKPD was in the